Human gingival fibroblast secretome accelerates wound healing through anti-inflammatory and pro-angiogenic mechanisms - Parinaz Ahangar (Nature Portfolio, 2020)
Abstract Healing of the skin and oral mucosa utilises similar mechanisms of tissue repair, however, scarring and the rate of wound closure is vastly superior in the oral cavity suggesting differences between these two environments. One key difference is the phenotype of dermal fibroblasts compared to fibroblasts of gingival tissues. Human gingival fibroblasts (hGFs) are undifferentiated cells with multi-differentiation and self-renewal capacities. This study aimed to examine if delivering hGFs or their secretome, contained in hGF-conditioned media (hGF-CM), would improve healing of the skin and recapitulate features of oral healing. Human fibroblasts, keratinocytes and endothelial cells were first treated with hGF-CM and showed improved migration, proliferation and angiogenic functions. A significant reduction in macroscopic wound area and histologic dermal wound width, as well as an increased rate of re-epithelialisation, were observed in both hGFs and hGF-CM treated murine excisional wounds. This improvement was associated with reduced inflammation, increased angiogenesis and elevated collagen deposition. These findings demonstrate that treatment of dermal wounds with either hGFs or hGF-CM may provide beneficial gingival-like properties to dermal wounds and may be a potential opportunity for improving healing of the skin.